Assessment of glomerular and tubulointerstitial apparatus state depending on the level of the natriuretic peptide in hypertension patients - A. I. Chernyavina (Российский кардиологический журнал)
Aim. To assess the state of the glomerular and tubulointerstitial apparatus depending on the level of the N-terminal pro-brain natriuretic peptide (NT-proBNP) in patients with hypertension (HTN).Material and methods. The study included 119 patients with stage I-II HTN (target organ damage classification). We determined the cystatin C level, glomerular filtration rate (GFF) using the CKD-EPI equation, neutrophil gelatinase‐associated lipocalin (NGAL) and NT-proBNP levels; echocardiography and sphygmoplethysmography was performed. In the first analysis, patients were divided into two groups depending on the NT-proBNP level. Group 1 (n=32) consisted of patients with NTproBNP level >125 pg/ml, group 2 (n=87)  — with NT-proBNP level <125 pg/ml. Empirically, the NT-proBNP cutoff point (75 pg/ml) was found to assess the role of cystatin C. The first group included 41 patients with NT-proBNP level >75 pg/ml, the second group — 78 patients with NT-proBNP level <75 pg/ml.Results. In the group 1 (NT-proBNP >125 pg/ml) the NGAL concentration was significantly higher than in the group 2: 2,50 [1,90;2,85] vs 1,30 [0,9;2,0] ng/ml, respectively (p=0,022). Patients in the groups did not significantly differ in the cystatin C levels and GFR (p=0,099 and p=0,090, respectively). When dividing patients according to the NT-proBNP cutoff point (75 pg/ml), the following data were obtained. The concentration of cystatin C in the first group with NT-proBNP >75 pg/ml was 1041,50 [995,00;1185,00] vs 964,30 [801,00;1090,00] ng/ml in the second group (p=0,034). Patients in the groups significantly differed in GFR (p=0,027). A correlation analysis revealed a moderate, direct relationship of NT-proBNP with cystatin C (r=0,32; p<0,005) and NGAL levels (r=0,36; p<0,05), as well as a moderate, inverse relationship with GFR (r=-0,35; p<0,005).Conclusion. NT-proBNP determination can be used as an integrative risk stratification tool for glomerular and tubulointerstitial injury in HTN patients.